On the Twa-Bantu intercommunity conflict in the province of Tanganyika: attempted solutions - C.T. AMURI KAMAKUMBI YAULI, (IJRDO - Journal of Social Science and Humanities Research, 2025)
The Twa are a marginalized indigenous minority while the Bantus are mainly farmers who have settled in the province of Tanganyika. The conflict between these two groups stems from historical tensions related to land, natural resources and access to public services.The study explores the deep roots of the conflict and examines the different attempted solutions that have been put in place to reduce tensions and promote peaceful coexistence between the two communities. Suggested approaches include the promotion of intercommunity dialogue, mediation by neutral third parties, equitable sharing of resources and economic opportunities, as well as reconciliation and transitional justice measures.We also analyzed the challenges and obstacles that hinder the lasting resolution of the conflict, such as discrimination, social exclusion, socio-economic inequalities and weak governance. They stressed the importance of taking into account the needs and perspectives of local communities in the formulation of policies and programs aimed at preventing conflicts and promoting social cohesion.In conclusion, this research highlights the complexity of intercommunity conflicts and the importance of implementing inclusive and participatory approaches to build lasting and harmonious peace between the Twa and the Bantous in the province of Tanganyika. It also highlights the need for collective and coordinated action by local authorities, civil society organizations and international actors to support reconciliation and conflict resolution efforts in the Province.